Kepemimpinan Kepala Sekolah dan Pengembangan Kompetensi Guru Pendidikan Agama Islam: Analisis Konseptual Berbasis Kajian Pustaka - Ahmad Ridwan; Muhammad Raihan Akbar; Nur Mila Maddu; Rizqi Firmansyah; Wahyu Kurniawan (MAN 4 Kota Pekanbaru, 2025)
This study aims to describe the leadership strategies of school principals in enhancing the competence and performance of Islamic Religious Education (IRE) teachers. Using a descriptive qualitative approach through a literature review, this research analyzes scholarly works related to educational leadership and teacher professional development. The findings indicate that principals play a crucial role through formal strategies (training and certification), non-formal strategies (workshops, in-house training, and micro-teaching), and collaborative strategies (Professional Learning Communities and MGMP). The implementation of coaching and mentoring also contributes significantly to improving teachers’ pedagogical and professional competencies as well as the quality of IRE instruction. In conclusion, effective and sustainable school principal leadership serves as a key factor in strengthening teacher quality and enhancing IRE learning in schools.